2021
DOI: 10.1073/pnas.2110004118
|View full text |Cite
|
Sign up to set email alerts
|

EIN3 and RSL4 interfere with an MYB–bHLH–WD40 complex to mediate ethylene-induced ectopic root hair formation in Arabidopsis

Abstract: The alternating cell specifications of root epidermis to form hair cells or nonhair cells in Arabidopsis are determined by the expression level of GL2, which is activated by an MYB–bHLH–WD40 (WER–GL3–TTG1) transcriptional complex. The phytohormone ethylene (ET) has a unique effect of inducing N-position epidermal cells to form root hairs. However, the molecular mechanisms underlying ET-induced ectopic root hair development remain enigmatic. Here, we show that ET promotes ectopic root hair formation through dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
1
31
1
Order By: Relevance
“…These findings contrast with other processes in which higher doses of ACC can affect development without conversion to ethylene, especially when the ACC oxidase enzyme is limited (Li et al, 2021; Polko and Kieber, 2019; Van de Poel, 2020; Vanderstraeten et al, 2019). We also do not see ectopic root hair formation in response to these short term and low dose treatments with ACC and ethylene, as reported recently when seedlings were treated with 10ppm ethylene for 2 days (Qiu et al, 2021), which is a 12-fold longer and 20-fold higher concentration.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings contrast with other processes in which higher doses of ACC can affect development without conversion to ethylene, especially when the ACC oxidase enzyme is limited (Li et al, 2021; Polko and Kieber, 2019; Van de Poel, 2020; Vanderstraeten et al, 2019). We also do not see ectopic root hair formation in response to these short term and low dose treatments with ACC and ethylene, as reported recently when seedlings were treated with 10ppm ethylene for 2 days (Qiu et al, 2021), which is a 12-fold longer and 20-fold higher concentration.…”
Section: Discussionsupporting
confidence: 89%
“…Downstream of RHD6, the RSL4 TF acts to define final root hair length based on its level of expression (Datta et al, 2015; Mangano et al, 2017). Previous work has shown that EIN3 physically interacts with RHD6 to form a transcriptional complex that coactivate RSL4 to promote root hair elongation (Feng et al, 2017), and that EIN3 and RSL4 both act to downregulate GL2 expression to drive ectopic root hair formation with long term treatments with high levels of ethylene (Qiu et al, 2021). It has also been shown that auxin treatment results in increased RSL4 transcript abundance, which binds to the promoters of RBOH and four class III peroxidase ( PRX ) genes, including PRX44 , to drive ROS synthesis in root hair cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, exogenous ACC treatment was also able to induce the formation of ectopic root hairs where non-treatment plants produced non-hair cells ( Tanimoto et al, 1995 ). Recent study indicates that ETH induces the formation of ectopic root hairs by activating the transcription factor of ethylene signaling ETHYLENE INSENSITIVE 3 (EIN3)/EIN3-LIKE1 (EIL1) and reducing the transcription level of root hair growth inhibitor GL2 ( Qiu et al, 2021 ). EIN3 affects the formation of the WER-GL3-TTG1 complex by competing with GL3 for binding to TTG1, which in turn reduces the transcription of GL2 by decreasing the formation of the WER-GL3-TTG1 complex ( Qiu et al, 2021 ).…”
Section: Eth Regulation Of the Growth And Development Of Plant Root Hairmentioning
confidence: 99%
“…Recent study indicates that ETH induces the formation of ectopic root hairs by activating the transcription factor of ethylene signaling ETHYLENE INSENSITIVE 3 (EIN3)/EIN3-LIKE1 (EIL1) and reducing the transcription level of root hair growth inhibitor GL2 ( Qiu et al, 2021 ). EIN3 affects the formation of the WER-GL3-TTG1 complex by competing with GL3 for binding to TTG1, which in turn reduces the transcription of GL2 by decreasing the formation of the WER-GL3-TTG1 complex ( Qiu et al, 2021 ). These results suggest that ETH is involved in regulating the fate determination of root hair cells, but the underling molecular regulation mechanism remains unclear.…”
Section: Eth Regulation Of the Growth And Development Of Plant Root Hairmentioning
confidence: 99%